Idarucizumab more effectively reverses the anticoagulant effects of dabigatran acylglucuronide than dabigatran - Jong-Min Kim; Young Yoon Bang; Kyoung-Ah Kim; Jin-Woo Park; Ji-Young Park (Scientific Reports)
Abstract Dabigatran acylglucuronide, an active metabolite of dabigatran, exhibits higher plasma concentrations and distinct anticoagulant effects compared to dabigatran, suggesting that it may play a more significant role in overall anticoagulant activity than previously assumed. Idarucizumab, a monoclonal antibody fragment, binds to both free and thrombin-bound dabigatran, neutralizing its anticoagulant effects. However, its efficacy in reversing anticoagulation induced by dabigatran acylglucuronide remains unclear. This study aimed to evaluate whether idarucizumab differentially reverses the anticoagulant effects of dabigatran and dabigatran acylglucuronide. In vitro experiments were conducted using blood from healthy, drug-free donors. Plasma samples were spiked with either dabigatran or dabigatran acylglucuronide, followed by idarucizumab. Standard coagulation assays, including prothrombin time (PT), activated partial thromboplastin time (aPTT), thrombin time (TT), as well as thrombin generation assays (TGA), were performed. At a concentration of 1 µM, idarucizumab demonstrated significantly greater reversal of dabigatran acylglucuronide-induced anticoagulation than that of dabigatran in PT, aPTT, and TT assays. Consistently, TGA showed stronger neutralization of dabigatran acylglucuronide, with IC50 values for Cmax, endogenous thrombin potential, and lag time at least 2.0-fold higher than those of dabigatran. These findings indicate that idarucizumab exerts a more potent reversal effect on dabigatran acylglucuronide compared to dabigatran.